Penerapan Metode MAUT Dalam Sistem Pendukung Keputusan Pemberian Bantuan Jasa Pada Kelurahan - Elwin Gea; Fabyen Sabillah Chan (TIN: Terapan Informatika Nusantara, 2023)
Aid is a program designed to help people who need it because they are in some kind of difficulty in ringing in their bebans. On this basis, a bantuan could consist of knowledge, a building, a piece of property, and even money or other benefits related to a previously granted jasa. Pengambilan keputusan adalah memilih a few available backup plans in order to accomplish one or a few previously set goals. According to McLeod, the keputus system is a particular system that is based on structure and uses data and a model.computer that produces a variety of alternative ideas for use by managers to assist them in handling a variety of problems that are poorly structured or not at allBased on the evaluation of alternative data and criteria using the Maut method, the model can be applied to four alternative data with the highest level of preferred outcome as shown below. : A7 Patience baringin manurung with a score of 0.733 A1 on behalf of Martumpal p hutajulu with a score of 0.465, A5 on behalf of pineeria simanungkalit with a score of 0.365, A3 on behalf of Janter lubis with a score of 0.344. So the MAUT (Multi Attribute Utility Theory) method can be used in solve the problem of selecting church officials who are eligible to receive merit assistance